In vitro and in vivo effects of ribavirin on human respiratory epithelium. Issue 2 (February 1990) - Han, L Y; Wilson, R; Slater, S; Rutman, A; Read, R C; Snell, N J; Cole, P J
Abstract : The effects of ribavirin, a broad spectrum antiviral agent, on the structure and function of normal human nasal epithelium have been studied in vitro, as has also the in vivo effect of treatment with nebulised ribavirin on nasal mucociliary clearance of saccharin in four patients. Ciliary beat frequency was measured by a photometric technique, and changes in epithelial and ciliary ultrastructure were assessed by transmission electron microscopy. Ribavirin solution at the recommended concentration of 20 mg/ml had no adverse effects on ciliary activity in vitro; at concentrations of 50 mg/ml and above it slowed ciliary beating significantly and at 60 mg/ml caused ciliostasis associated with epithelial disruption. Nasal inhalation of ribavirin at 60 mg/ml for up to 20 minutes, however, did not slow nasal mucociliary clearance, nor did it adversely affect the ciliary beating or structure of nasal ciliated epithelium examined in vitro immediately after inhalation.